2015
DOI: 10.1002/srin.201500022
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties and Solidification Defects of Fe-22Mn-0.7C TWIP Steel

Abstract: The thermophysical properties and solidification defects of Fe-Mn-C twinning-induced plasticity (TWIP) steel have been experimentally studied. The liquidus and solidus of Fe-22Mn-0.7C TWIP steels are measured to be 1380 AE 10 and 1270 AE 108C, respectively. The thermal conductivity of Fe-22Mn-0.7C steel is the lowest compared with that of carbon steel Q235 and stainless steels 304 and J4. Combined with the highest thermal expansion coefficient of TWIP steel, internal cracking is apt to occur due to the extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Pichler pointed out that the macro‐segregation of solute elements will affect the stability of austenite and delay the growth of ferrite, thus had influence on the final solidification structures. Some studies have shown that in austenite steel with high Mn content, Mn will segregate between the dendrites in the solidification process. Markus Daamen et al observed the similar positive segregation tendency of Mn in a Fe–29Mn–0.3C steel produced via strip casting.…”
Section: Introductionmentioning
confidence: 99%
“…Pichler pointed out that the macro‐segregation of solute elements will affect the stability of austenite and delay the growth of ferrite, thus had influence on the final solidification structures. Some studies have shown that in austenite steel with high Mn content, Mn will segregate between the dendrites in the solidification process. Markus Daamen et al observed the similar positive segregation tendency of Mn in a Fe–29Mn–0.3C steel produced via strip casting.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the fusion line was not the poorest zone, which was quite different from the ferritic steels like low-alloy high-strength steels [ 29 ]. It was because that the weld metals were designed to have the similar chemical composition (in Table 5 ) with the base metal (in Table 2 ), which allowed the weld pool to solidify with the same phase of austenite and the weld metal not to undergo any phase transformations during continuous cooling [ 30 ]. Although the grain coarsened at FL, the coarse grain was fortunately not detrimental to cryogenic toughness for high-Mn steel [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The temperature-dependent thermal conductivity was adopted from experimental measurements on a similar alloy. 73 Since the laser radiation interacts mostly with the liquid melt pool during LPBF, 74 an absorption coefficient of 0.41 for liquid iron irradiated by an Nd-YAG laser was chosen. 75 Five scanning tracks with a bi-directional scan strategy were modeled.…”
Section: Thermal Fieldmentioning
confidence: 99%